Long-term psychosocial consequences of whole-body magnetic resonance imaging and reporting of incidental findings in a population-based cohort study - Korbmacher-Böttcher, Dorina; Bamberg, Fabian; Peters, Annette; Linkohr, Birgit; Ladwig, Karl-Heinz; Schwettmann, Lars; Weckbach, Sabine; Schlett, Christopher L.; Rospleszcz, Susanne (Diagnostics, 2022)
Management of radiological incidental findings (IF) is of rising importance; however, psychosocial implications of IF reporting remain unclear. We compared long-term psychosocial effects between individuals who underwent whole-body magnetic resonance imaging (MRI) with and without reported IF, and individuals who did not undergo imaging.